The Effect of Jakarta Composite Stock Price Index, Jakarta Interbank Offered Rate as Determination Factors Fluctuations in Net Asset Value of Mixed Mutual Funds - Vivin Hanitha; Berlin Silaban; Tri Angreni (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
The purpose of this study is to define the factors that influence the Mixed Mutual Funds including the Jakarta Interbank Offered Rate and the Composite Stock Price Index. The research method used is purposive sampling by taking data on price movements of mutual funds published by PT Ashmore Asset Management Indonesia Tbk where Mutual funds originating from the period January 1, 2021 to December 31, 2021 and listed on the IDX, consist of 245 daily data. The test method used is descriptive statistical method using sample data from JCI and JIBOR where the results obtained from the calculation of this analysis are JCI and JIBOR have a positive and significant effect on the performance of the Net Asset Value of Mutual Funds, with a coefficient of determination close to 0.6526 or 65, 26%, which means that NAV is influenced by the movement of JCI and JIBOR. While the remaining 34.74% is explained by variables not included in this study.